2017
DOI: 10.2217/pgs-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of SLCO1B1 and ABCB1 Genotypes on the Pharmacokinetics of Simvastatin, in Relation to CYP3A4 Inhibition

Abstract: Aim:To investigate the combined effects of SLCO1B1 and ABCB1 genotypes on the pharmacokinetics of simvastatin and its active metabolite simvastatin acid, in relation to CYP3A4 inhibition. Methods: We conducted a single-dose pharmacokinetic study of simvastatin in 26 healthy volunteers screened for their SLCO1B1 c.521T>C and ABCB1 c.1236C>T-2677G>T-3435C>T genotypes, with and without amlodipine pretreatment. The genetic effects and drug-interaction effect on simvastatin pharmacokinetic parameters were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 33 publications
2
39
1
1
Order By: Relevance
“…For instance, reduced CYP3A4 and SLCO1B1 activities can both result in increased AUC of the substrate drug and a greater harm would be anticipated. Carriers of the TC genotype of SLCO1B1 rs4149056 (T>C) variant who are treated with amlodipine (CYP3A4 inhibitor) experienced a 90% increased simvastatin AUC compared with subjects not treated with amlodipine and wild-type for rs4149056 [87]. A similar scenario was reported with other two case reports (see Supplementary Table 1) [88,89].…”
Section: Ddgis and Challenges In Clinical Practicesupporting
confidence: 80%
“…For instance, reduced CYP3A4 and SLCO1B1 activities can both result in increased AUC of the substrate drug and a greater harm would be anticipated. Carriers of the TC genotype of SLCO1B1 rs4149056 (T>C) variant who are treated with amlodipine (CYP3A4 inhibitor) experienced a 90% increased simvastatin AUC compared with subjects not treated with amlodipine and wild-type for rs4149056 [87]. A similar scenario was reported with other two case reports (see Supplementary Table 1) [88,89].…”
Section: Ddgis and Challenges In Clinical Practicesupporting
confidence: 80%
“…The interest in SLCO1B1 as a marker of pharmacogenetics research has increased rapidly during the last decade. In previous studies, the non-coding SLCO1B1 c.521T>C single nucleotide poly- morphism has been shown to be significantly associated with an increased risk of statin-induced adverse reactions [4,5]. Individuals carrying 1 (T/C-heterozygotes) and 2 (C/C-homozygotes) SLCO1B1 c.521C alleles are reported to have a 4-and 16-fold higher risk of dose-dependent myopathy after statin intake compared to T/T-homozygotes, respectively [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that gene polymorphisms in uence T2DM therapeutic effects [16][17][18][19][20][21][22][23]. SNPs in the HTR3B, HTR7 or ABCB1 genes were associated with myalgia or liver injury [16,22].…”
Section: Resultsmentioning
confidence: 99%
“…APOE and HMGCR mutations were associated with LDL-C levels [17,20]. CETP, KIF6, SLCO1B1, and CYP2C9*3 were related to the statin effect [18,19,21,23]. To check genetic polymorphisms in Chinese T2DM patients, HTR3B (rs2276307, A > G), APOE (rs7412, c.526C > T), APOE (rs429358, c.388T > C), CYP2C9*3 (rs1057910, c.1075A > C), KIF6 (rs20455, c.2155T > C), HMGCR (rs17238540, T > G), HMGCR (rs17244841, A > T), ABCB1 (rs2032582, c.2677G > T/A), HTR7 (rs1935349, C > T), SLCO1B1 (rs4149056, c.521T > C), and CETP (rs708272, G > A) were detected by the MassARRAY system before patients underwent statin therapy ( Fig.…”
Section: Resultsmentioning
confidence: 99%